2020
DOI: 10.1177/1708538120921316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug-coated balloons versus bare-metal stents on endothelial function in patients with severe lower limb peripheral artery disease

Abstract: Background Research shows impaired endothelial function in patients with vascular diseases and improved endothelial function following revascularization and medical treatment. There is, however, a dearth of data on the effects of different endovascular therapeutic strategies on endothelial function. We sought to compare the effects of two endovascular strategies of drug-coated balloons versus stenting on endothelial function. Methods The reactive hyperemia index, the ankle-brachial index, and the toe-brachial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Management strategies for DFU include prevention and control of infection, offloading pressure, removing necrotic tissue, applying appropriate dressings and medications, ensuring adequate blood flow, controlling blood sugar. [5][6][7] The high cost of DFU to both patients and healthcare systems necessitates instituting preventive and control measures at the earliest opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies for DFU include prevention and control of infection, offloading pressure, removing necrotic tissue, applying appropriate dressings and medications, ensuring adequate blood flow, controlling blood sugar. [5][6][7] The high cost of DFU to both patients and healthcare systems necessitates instituting preventive and control measures at the earliest opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of living standards and the aggravation of the aging population, the incidence of ASO is increasing year by year and has become one of the major diseases threatening the life safety of patients. As a classic intramural treatment, BMS materials have the advantages of flexibility, high biocompatibility, and good support and have good clinical efficacy in improving the short-term patency rate after PTA and improving the patient's postoperative motor function [ 9 ]. With the development of endovascular treatment technology, the advantages of DCB in the clinical treatment of ASO are highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular procedures in all studies included the use of balloon catheters and stents when indicated. One study [12] compared the DCB (Drug-Coated Balloon) to POBA (Percutaneous Old Balloon Angioplasty). The results of PTA were analyzed based on the occurrence of restenosis (i.e.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Two studies [12,14] included in this review primarily compared RHI values before and after PTA, as summarized in Table 2. Shafe et al [12] measured RHI after endovascular revascularization in two groups of patients: DCB-treated patients and POBA with stenting-treated patients.…”
Section: Reactive-hyperemia Indexmentioning
confidence: 99%
See 1 more Smart Citation